Influence of environmental pressure and inhibitory control capacity on anxiety, mental workload and shooting performance in multitasking basketball contexts - Gutiérrez-Capote, A.; Jiménez-Martínez, J.; Madinabeitia, I.; Torre, E.; Leicht, A. S.; Botía, M.; Alarcón, F.; Cárdenas, D. (Psychology of Sport and Exercise, 2025)
Background Basketball shooting performance is crucial for match outcomes, often influenced by environmental pressure and anxiety. This study investigates how increased task demands and outcome consequences affect anxiety, mental workload, and shooting performance in multitasking basketball contexts. Additionally, it examines the moderating role of inhibitory control (IC) on these effects.